PENGARUH BOKHASI ECENG GONDOK PADA TANAMAN SELADA ( Lactuca sativa L.) - Seprita Lidar; R. Kalista R. Kalista (Jurnal Ilmiah Pertanian, 2016)
The issue of organic farming lately indeed began to grow back more and more people will realize the importance of health and quality of food consumed. In addition to health reasons, organic farming is also believed to be environmentally friendly because it can minimize the use of chemicals in the production process, due to the use of chemical fertilizers continuously with increasing doses it can cause the soil to be loud and disturbed soil nutrient balance. Market demand for vegetable crops, especially lettuce is usually consumed raw continue to rise, especially lettuce plants are fertilized with organic fertilizer. Land in the city of Pekanbaru classified as land Podsolid Red Yellow (FMD) is organic matter content and nutrient relatively low, then one attempt to overcome this problem is by fertilizing safe for plants and soil is fertilizer bokhasi hyacinth that contains nutrients N , P and K, also take advantage of in the environment that would otherwise be used will cause pollution in the waters. From research conducted bokhasi provision of water hyacinth significantly affect the growth and production of lettuce plants with the best dose is 2000 g / m2.